2021
DOI: 10.3390/s21061994
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Planting Structures of Different Complexity from UAV Multispectral Images

Abstract: This study explores the classification potential of a multispectral classification model for farmland with planting structures of different complexity. Unmanned aerial vehicle (UAV) remote sensing technology is used to obtain multispectral images of three study areas with low-, medium-, and high-complexity planting structures, containing three, five, and eight types of crops, respectively. The feature subsets of three study areas are selected by recursive feature elimination (RFE). Object-oriented random fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
1
15
0
Order By: Relevance
“…Many experiments showed that when ntree was 50, the error gradually converges and tended to be stable. Mtry was the square root of the total feature [32].…”
Section: Random Forest Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many experiments showed that when ntree was 50, the error gradually converges and tended to be stable. Mtry was the square root of the total feature [32].…”
Section: Random Forest Methodsmentioning
confidence: 99%
“…Due to years of uncontrolled irrigation from the Yellow River, the groundwater level in this region is high and the soil salinity degree is high. As a result, only salinity resistant crops can be planted in this region, such as maize and sunflower, among which the largest planting scale is sunflower [31,32].…”
Section: Selection Of Study Areasmentioning
confidence: 99%
See 1 more Smart Citation
“…Before considering the details, the different mentions of intercropping in remote sensing literature are summarised. Q. Ma et al [19] compiled information on several papers mentioning that crop identification in intercropping of multiple crops makes it difficult to attain high accuracy and that most studies focus on three to five different crops. They also mention that, although spectral and texture features calculated with UAV multispectral remote sensing data combined with an object-oriented Support Vector Machine (SVM) obtain high accuracies in mono-crop systems (up to 94% in maize [20]), there is significant interferences in mixed crop and intercropping.…”
Section: Comparison Of Results With Literaturementioning
confidence: 99%
“…Drones are rapidly evolving in the field of agriculture and can perform numerous tasks, such as weed mapping [ 14 ], soil and crop status monitoring [ 15 ], pesticide spraying [ 16 ], diagnosis of insect pests [ 17 ], and artificial pollination [ 18 ].…”
Section: Related Workmentioning
confidence: 99%